A monolith electrode featuring FeS2 embedded in porous carbon nanofibers for efficient hydrogen evolution. (20th July 2022) - Li, Yuting; Ma, Weihua; Zeng, Yiqing; Chen, Xiaoyang; Wang, Juan; Zhong, Qin
Abstract: Constructing electrode materials embracing with high effectivity and durable stability is of vital importance for hydrogen evolution reaction (HER) in electrochemical water splitting. Herein, a monolith electrode is designed with FeS2 nanoparticles embedded in porous carbon nanofibers (FeS2 @CNFs) via an in-situ electrospinning strategy, which is directly used as an efficient electrode for HER without any extra-substrates. Such monolithic electrode eliminates interface problems between active catalysts and carriers and expends more intrinsic catalysis regions, which effectively shortens the pathway of electron/ mass transport. The FeS2 @CNFs electrode displays good HER activity only with an overpotential of 168 mV at 10 mA cm −2 . It is worth noting that this monolith electrode shows the excellent HER stability for nearly a week in 1 M KOH without any destruction of fibrous structure. Such considerable activities can be ascribed to the interwoven nanofiber-meshes that engineer the self-supportive architecture with stable strength and the carbon-encapsulation structure that prevents FeS2 from collapsing. The woven meshes and porous structure allow the sufficient penetration of electrolyte and fast gas diffusion. This work provides a valuable reference for rationally designing a monolith electrode effectively for gas-involved electrochemical application. Graphical abstract: Image, graphical abstract